Analysis of complex treatment of patients with osteoarthritis combined with hypertension using algofunctional leken index - Bondar, М. V.; Sroganova, T. V.; Kuznetsova, L. P.; Строгонова, Тетяна Василівна (Запорізька медична академія післядипломної освіти, 2020)
Among diseases that significantly affect health, osteoarthritis ranks 4th in women and 8th in men. In persons of both sexes over 70 years old, osteoarthritis occurs in almost everyone, and in the last decade its prevalence has been steadily increasing. The social significance of osteoarthritis is determined by the growth of the associated disability and disability, especially in older age groups, as well as a sharp decrease in the quality of life in this disease.
Keywords: тези